Code-Mixing in Sabah and Sarawak English Short Stories - Campbell, Yvonne Michelle; Charles, Fazira Bukas (Trends in Undergraduate Research, 2023)
This study explored code-mixing in selected English short stories from Sabah and Sarawak. It examined the types of code-mixing found in these short stories and the basis for these code-mixing. 20 short stories were selected from two anthologies, “Chronicles of KK” and “Short Stories from Sarawak: Death of a Longhouse & Other Stories”. This study applied a qualitative research method, and the data were analysed using Musyken’s (2000) and Hoffman’s (1991) theories. Two types of code-mixing were found in the short stories which are insertion, and alternation, with insertion being the most common type found, especially lexical items from Sabah and Sarawak’s local or indigenous languages. The study discovered that the reason these code-mixing was used was to talk about a particular topic, to clarify the speech content for interlocutor, to express group identity, to repeat something for clarification and as a form of interjection.